2011
DOI: 10.1007/s10562-011-0555-9
|View full text |Cite
|
Sign up to set email alerts
|

A One-Pot Two-Step Approach for the Catalytic Conversion of Glucose into 2,5-Diformylfuran

Abstract: One-pot two-step synthesis of DFF was achieved by catalytic conversion of glucose over CrCl 3 Á6H 2 O/NaBr//NaVO 3 Á2H 2 O catalysts, and a DFF yield of 55% based on glucose was obtained. This glucose conversion process is characterized by the abundance and low cost of starting material and no need for HMF separation or purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Their catalytic system needs separation of the first product (HMF) and the acidic ion-exchange resin before performing the oxidation reaction. On the other hands, our catalytic system enables to synthesize DFF from fructose without separation of the first acid catalyst (Amberlyst-15) from the reaction mixture before the subsequent oxidation by Ru/HT, as shown in Table 12 Furthermore, we demonstrated one-pot synthesis of DFF from glucose based on our findings that a combination of solid acid (Amberlyst-15) and base (HT) catalyst afforded HMF from glucose as well as fructose via glucose-fructose isomerization by base and successive fructose dehydration by acid (vide supra) [86,207]. 1 Therefore, one-pot synthesis of DFF from glucose by using a combination of triple heterogeneous catalysts, HT, Amberlyst-15, and Ru/ HT has been examined.…”
Section: Synthesis Of Dialdehyde Via Selective Oxidations Of Functionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their catalytic system needs separation of the first product (HMF) and the acidic ion-exchange resin before performing the oxidation reaction. On the other hands, our catalytic system enables to synthesize DFF from fructose without separation of the first acid catalyst (Amberlyst-15) from the reaction mixture before the subsequent oxidation by Ru/HT, as shown in Table 12 Furthermore, we demonstrated one-pot synthesis of DFF from glucose based on our findings that a combination of solid acid (Amberlyst-15) and base (HT) catalyst afforded HMF from glucose as well as fructose via glucose-fructose isomerization by base and successive fructose dehydration by acid (vide supra) [86,207]. 1 Therefore, one-pot synthesis of DFF from glucose by using a combination of triple heterogeneous catalysts, HT, Amberlyst-15, and Ru/ HT has been examined.…”
Section: Synthesis Of Dialdehyde Via Selective Oxidations Of Functionmentioning
confidence: 92%
“…Very recently, Hu et al reported the direct synthesis of DFF from glucose by the combination of CrCl 3 and NaVO 3 from HMF formation and HMF oxidation, respectively[207].…”
mentioning
confidence: 99%
“…The yields of DFF from fructose and glucose were 49% and 25%, respectively. Xiang et al [107] investigated the synthesis of DFF from glucose using the one-pot two-step approach over CrCl3·6H2O/NaBr/NaVO3·2H2O catalysts. A DFF yield of 55% based on glucose was obtained.…”
Section: Catalytic Oxidation Of Hmf To Dffmentioning
confidence: 99%
“…The DFF yields were 25 % and 49 %, respectively, when using glucose or fructose as starting materials. In our previous work, [23] we used CrCl 3 ·6 H 2 O/NaBr as co-catalysts for the simultaneous isomerization/dehydration step, while NaVO 3 ·2 H 2 O was used as catalyst for the oxidation step, realizing the twostep conversion of glucose to DFF with a maximum yield of 55 % in N,N-dimethylacetamide. Recently, Fu and coworkers [24] reported the joint utilization of Fe 3 O 4 -SBA-SO 3 H and K-OMS-2 catalysts for the two-step conversion of fructose to DFF in dimethyl sulphoxide (DMSO) under oxygen flow (10 mL min À1 ).…”
Section: Introductionmentioning
confidence: 99%